Construction of Particlboard Using Tannin-Based Phenol Adhesive - ُSima Sepahvand; Meysam Zahedi; Samaneh vilki; Taghi Tabarsa (تحقیقات علوم چوب و کاغذ ایران, 2012)
Tannins are the most desirable natural, renewable phenolic components which obtained from plant resources. The phenolic nature of tannins causes that this materials react with formaldehyde and form tannin-formaldehyde resins. In this study, the raw materials of wheat straw and forest woods were used for producing of particleboard (with a ratio of about 50 to 50 percent) using phenol formaldehyde based on tannin. Tannin as a powder was added at 10 and 20 percent (based on dry weight of resin solution) to formalin 35% for glue making. Particleboards were made at two range of thickness, 10 and 16 mm and their properties of including bending strength, modulus of elasticity, internal bonding, thickness swelling and water absorption were measured. The results from this investigation showed that the strength properties of the made boards from combined wood chips were lower than those from pure wood chips. Also, increasing of tannin usage into phenol formaldehyde caused to increase internal bonding or adhesion, swelling and water absorption (2 and 24 hours) of the boards.